Effect of SMAW Process Parameters on Hardness, Temperature Distribution, and Micro–Macro Structure of A36 Steel Welded Joints - Desrilia Nursyifaulkhair; Priyambodo Nur Ardi Nugroho; Dianita Wardani; Kharismajid Kharismajid; Mochammad Karim Al Amin; Muhamad Eko Nur Khazi (Universitas Negeri Jakarta, 2026)
The outer shell of an ISO tank plays a critical role in maintaining the integrity of its contents by withstanding temperature fluctuations, pressure, and radiation. Research on the fabrication of liquefied natural gas (LNG) tank outer shells therefore provides both scientific and practical value, particularly in ensuring mechanical reliability and structural performance. This study investigates the welding of American Society for Testing Materials (ASTM) A36 steel plates using shielded metal arc welding (SMAW) and evaluates the effect of welding parameters on mechanical and microstructural properties. Four specimens were prepared by varying welding current at 70 and 80 A on plate thicknesses of 4 and 12 mm. The results indicate that both current and thickness significantly influence the weld zone microstructure, with transformations from ferrite–pearlite in the base metal to widmanstätten and acicular ferrite in the weld metal. In terms of mechanical performance, the highest hardness value of 198.387 HVN was recorded in the 4 mm specimen welded at 70 A, demonstrating the strong dependence of hardness on combined current and thickness conditions. These findings contribute to optimizing welding parameters for the safe and reliable application of LNG tank outer shells.